Association between serum albumin and severe impairment of activities of daily living in patients with stroke: a cross-sectional study - Ranran Bi; Yupeng Shi; Manrong Li; Xiaochen Liu; Zhenchao Ma; Yiqing Huang; Bingyin Liang; Fang Cui (Frontiers in Neurology)
PurposeThe relationship between serum albumin levels and severe limitations in ADLs among stroke patients remains unclear. Specifically, the dose–response relationship between the two needs further exploration. This study aims to provide further results.Materials and methodsThis study examined cross-sectional data from patients aged 18 years or older with a diagnosis of stroke confirmed by cranial CT or MRI within 24 h of admission, gathered from January 2020 to August 2022. Data included serum albumin levels, Barthel Index scores recorded after admission, and other essential variables.ResultsThe study comprised 2,393 stroke patients. After adjusting for confounding factors, the multivariate analysis revealed a 7% decrease in severe impairment of ADL after stroke for every unit (g/L) increase in serum albumin levels. Compared with individuals with lower serum albumin levels (Q1: ≤ 37.4 g/L), the adjusted odds ratios (OR) for severe of ADL impairment among stroke patients in Q2 (37.4–40.21 g/L), Q3 (40.21–42.80 g/L), and Q4 (≥42.8 g/L) were 0.68 (95% CI: 0.4–1.15, p = 0.148), 0.55 (95% CI: 0.32–0.97, p = 0.04), and 0.64 (95% CI: 0.37–1.15, p = 0.139), respectively. The relationship between serum albumin and severe impairment of ADLs in stroke patients showed an L-shaped curve (non-linear, p = 0.002), with an inflection point at 38.0 g/L. The OR for significant impairment of ADLs was 0.680 (95% CI: 0.568–0.814, p < 0.001) in participants with serum albumin levels <38.0 g/L. However, when serum albumin levels were greater than or equal to 38.0 g/L, the severe impairment of ADLs no longer decreased with rising serum albumin levels.ConclusionIn summary, an L-shaped connection with an approximate inflection point of 38.0 g/L was found between blood albumin levels and significant ADL impairment in stroke patients. The results of this study suggest that increasing serum albumin levels can significantly help improve the severity of ADL impairment in stroke patients, particularly those with serum albumin levels below 38.0 g/L.